Adverse cardiovascular outcomes between insulin-treated and non-insulin treated diabetic patients after percutaneous coronary intervention: a systematic review and meta-analysis. Issue 1 (December 2015) - Bundhun, Pravesh; Li, Nuo; Chen, Meng-Hua
Abstract Background Type 2 diabetes mellitus (DM) patients have worse adverse cardiovascular outcomes after Percutaneous Coronary Intervention (PCI). However, the adverse cardiovascular outcomes between insulin-treated and non-insulin treated DM patients have been a subject of debate. We sought to compare the short-term (<1 year) and long-term (≥1 year) cardiovascular outcomes between insulin-treated and non-insulin treated DM patients after PCI. Methods Medline and Embase databases were searched for studies by typing 'diabetes and percutaneous coronary intervention/PCI' or 'insulin-treated and non-insulin treated diabetes mellitus and PCI'. Endpoints included adverse cardiovascular outcomes reported in these DM patients during the corresponding follow-up periods. Odd Ratio (OR) with 95 % confidence interval (CI) was used to express the pooled effect on discontinuous variables and the pooled analyses were performed with RevMan 5.3. Results 21 studies have been included in this meta-analysis consisting of a total of 21, 759 diabetic patients (6250 insulin-treated and 15, 509 non-insulin treated DM patients). Short term mortality, myocardial infarction, target lesion revascularization, major adverse cardiac effects and, stent thrombosis were significantly higher in insulin-treated diabetic patients (OR 1.69, 95 % CI 1.40–2.04, p < 0.00001), (OR 1.40, 95 % CI 1.16–1.70, p = 0.0005), (OR 1.37, 95 % CI 1.06–1.76, p = 0.02), (OR 1.46, 95 % CI 1.22–1.76, p < 0.0001) and (OR 1.66, 95 % CI 1.16–2.38, p = 0.005) respectively. Long-term cardiovascular outcomes were also significantly higher in insulin-treated DM patients. Conclusion Insulin treatment in these DM patients was associated with a significantly higher short and long-term adverse cardiovascular outcomes after PCI compared to those DM patients not treated by insulin therapy.